Modelos de gestão da inovação: um estudo de casos em empresas brasileiras do setor petroquímico - Francini, William Sampaio (2012)
Innovation consists in pressing challenge for organizations of all sizes and missions. Given its relevance to the public and private organizations of different sizes, as well as for local, regional, national and international economies, innovation management is the core of this multiple case study. Innovation management and its alignment with business strategy may represent a significant competitive advantage. Through a systemic view on innovation management, it is possible that organizations generate benefits and externalities that can reach various actors and stakeholders involved in the process, such as employees, business partners, suppliers, users, customers and government agencies. From this perspective, innovation strategy is considered a central approach regarding business strategy. Our intent in undertaking this research is to understand the complexity and value of innovation processes in organizations and its effects as consequences of deliberate and emergent strategies. This research proposes a framework to be used by managers in process mapping of varying degrees of complexity, in order to support the management of product, process and administrative innovations in a structured manner, with special emphasis onto the innovation funnel model and its interface with information technology, as well as organizational and interorganizational processes, which may include external partnership in open innovation. Conjoint to theoretical research, we developed three case studies, which form the basis of this reference model. All cases include companies in the Brazilian petrochemical sector, being one of them a large company, Braskem SA, and two of them small businesses, respectively Hausthene Poliuretanos Ltda.and Prorevest Revestimentos de Poliuretanos e Peças Especiais Ltda. The reference framework proposed seeks to identify the necessary conditions – the innovation determinants – that enable the management of innovation in products, processes and administration, and its possible outcomes.